Screening of shallow groundwater in Aceh Besar and Banda Aceh Districts for contamination with heavy metals - Cut Yulvizar (Syiah Kuala University, 2011)
Tsunami devastated many water infrastructures including the wells. Tsunami areas, land use (rural and urban areas) and land management (agriculture land and home garden) can be leading heavy metals in water quality. The purpose of this research is to investigate how the Tsunami rehabilitation efforts affected the water quality of shallow groundwater by measuring the count of heavy metals (mercury, cadmium and lead by Atomic Absorption Spectrophotometer during the rainy and dry season. Forty-eight water samples’ of wells were collected to determine shallow groundwater from August 2007 to December 2007. The study includes interviews with the owners of the water facilities and sanitary inspection of shallow groundwater wells. The results show the presence Hg and most of Cd in well water are still below the regulatory acceptable limit by Ministry of Health R.I (2002). On the other hand, lead exceeds the regulatory acceptable limit